1994
DOI: 10.1038/jcbfm.1994.72
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Nitric Oxide Synthesis Inhibits Hippocampal Hyperemia in Kainic Acid-Induced Seizures

Abstract: Summary:We investigated whether the nitric oxide (NO) synthase inhibitor �-nitro-L-arginine methyl ester (L NAME) affects the cerebrovascular changes occurring in seizures induced by kainic acid (KA) in awake, sponta neously breathing rats. Blood flow and tissue P02 and Pco2 were continuously and simultaneously measured by mass spectrometry from a cannula chronically implanted into the dorsal hippocampus. L-NAME (20 mg/kg; n = 8) or saline (n = 9) was administered i.p. 30 min prior to i.p. KA (10 mg/kg) inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 43 publications
(12 reference statements)
1
15
0
Order By: Relevance
“…Superfusion with NA attenuated the local increases in LCBF, suggesting that the cerebrovasodilation elicited by focal epileptic seizures depends on NO production. Recent studies using systemic injection of NOS inhibitors (35,36) showed a reduction of the reactive hyperemia associated with generalized seizures, but their interpretation is complicated by the generalized vasoconstricValues are means ± SE. *P < 0.05, compared with the contralateral cortex (aCSF perfused) (Student's dependent t test).…”
Section: Discussionmentioning
confidence: 99%
“…Superfusion with NA attenuated the local increases in LCBF, suggesting that the cerebrovasodilation elicited by focal epileptic seizures depends on NO production. Recent studies using systemic injection of NOS inhibitors (35,36) showed a reduction of the reactive hyperemia associated with generalized seizures, but their interpretation is complicated by the generalized vasoconstricValues are means ± SE. *P < 0.05, compared with the contralateral cortex (aCSF perfused) (Student's dependent t test).…”
Section: Discussionmentioning
confidence: 99%
“…Recent experimental investigations have shown that NO might meet the essential criterion to function as a retrograde messenger for long term potentiation in hippocampal cells, a process known to be involved in mammalian learning and memory [24]. NO mediates changes in cerebral blood flow under certain physiological [25] and pathological conditions [26,27]. However, excessive production of NO has also been implicated in a number of pathophysiological conditions including stress [28].…”
Section: Introductionmentioning
confidence: 99%
“…injections of either L-NAME (10 mg/kg), L-NAME and L-arg (10 mg/kg and 300 mg/kg, respectively), or 7NI (40 mg/kg). At thesc dose ranges, 7NI and LNAME affect seizure activity, reactive hyperemia, and consequences in various adult rodent models of cpilepsy (24,(29)(30)(31)(32)(33) and, from 30 to 120 min after the injection, produce 50-85% inhibition of brain NOS (3334). The effect of r,-arg alone (300 mg/kg) was studied at 10 min before the first PTZ dose, to compensate for the quite rapid metabolism of L-arg, mainly through the urea cycle.…”
Section: Pharmacologic Treatmentsmentioning
confidence: 99%